The retrograde IFT dynein is required for normal function of diverse mechanosensory cilia in Drosophila - Sharma, Yashoda; Jacobs, Julie S.; Sivan-Loukianova, Elena; Lee, Eugene; Kernan, Maurice J.; Eberl, Daniel F. (Frontiers in Molecular Neuroscience, 2023)
Introduction Cilia biogenesis relies on intraflagellar transport (IFT), a conserved transport mechanism which functions bi-directionally to bring protein complexes to the growing ciliary tip and recycle signaling and transport proteins between the cilium and cell body. In Drosophila, anterograde IFT is critical for assembly of sensory cilia in the neurons of both chordotonal (ch) organs, which have relatively long ciliary axonemes, and external sensory (es) organs, which have short axonemal segments with microtubules in distal sensory segments forming non-axonemal bundles. We previously isolated the beethoven (btv) mutant in a mutagenesis screen for auditory mutants. Although many btv mutant flies are deaf, some retain a small residual auditory function as determined both by behavior and by auditory electrophysiology. Results Here we molecularly characterize the btv gene and demonstrate that it encodes the IFT-associated dynein-2 heavy chain Dync2h1. We also describe morphological changes in Johnston’s organ as flies age to 30 days, and we find that morphological and electrophysiological phenotypes in this ch organ of btv mutants become more severe with age. We show that NompB protein, encoding the conserved IFT88 protein, an IFT complex B component, fails to be cleared from chordotonal cilia in btv mutants, instead accumulating in the distorted cilia. In macrochaete bristles, a class of es organ, btv mutants show a 50% reduction in mechanoreceptor potentials. Discussion Thus, the btv-encoded Dync2h1 functions as the retrograde IFT motor in the assembly of long ciliary axonemes in ch organs and is also important for normal function of the short ciliary axonemes in es organs.